Economically Dependent Standard as a Criterion of Employment Rights for Semi-Employed Workers in Poland - Kobroń-Gąsiorowska, Łucja (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The current legal status protects only employees within the meaning of Art. 2 of the Labor Code, and in a small part of contractors, it contributes to the deterioration of the situation of semi-dependent/self-employed workers, resulting in effects that are entirely opposite to the intended ones, i.e., the inclusion of the axiology of the protective function into non-employee forms of work. Poland does not have its own scope of protective provisions similar to the labor code provisions that would apply to economically semi-dependent/self-employed workers. In this article, is analyzed the concept of the economically semi-dependent/self-employed as a starting point for granting them certain employment rights. Two main conclusions can be drawn: first, the economically semi-dependent self-employed is not an intermediate category between workers and the self-employed but a subcategory of the self-employed. Secondly, failure to grant them protection by Polish labor law will have a negative impact on the extension of collective rights of the self-employed.